(untitled) (Research, Society and Development, 2020)
The objective of the research was to extract betalains from beets root and to evaluate their potential as a dye and natural antioxidant in chicken bologna. Through the quantification of betalains by the phonophometric method, you can obtain a better extraction in aqueous, alcoholic, hydroalcoholic solvent in neutral pH and hydroalcoholic in pH 3. The optimized beet extractor was dried at 40 ° C, being analyzed or its theoretical content phenolic. Four mortadella formulations were made: MC (negative control) = addition of 0.05% synthetic dye, MBHT = addition of antioxidant BHT 0.01% and synthetic dye 0.05%, M4% = addition of 4% extract beet; M6% = addition of 6% extract beet. They were performed as lipid oxidation (TBARS), pH, water activity (Aa) and color (a *, L *, b *) analyzes for 45 days, evaluated by linear regression data. It was found that the best solvent was hydroalcoholic at neutral pH, resulting in 153.14 mg / L of betalains and 99.1 mg EAG / g of phenolic compounds. After a period of 45 days, the pH and Aa values did not change, there was an increase in the brightness of MC and M4%, a reduction in the red color by M6%, which suggests the degradation of betacyanins by the antioxidant activity and a decreasing yellow color by M4% and M6%, degradation of betaxanthines. At the end of the study, M4% and M6% had the lowest lipid oxidation values. These results confirmed the potential of betalains as dyes and natural antioxidants